2017
DOI: 10.1016/j.bbadis.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced PGE2 up-regulates Aβ production through PKA/CREB signaling pathway

Abstract: Ethanol abuse aggravates dementia-associated cognitive defects through the progression of Alzheimer's disease (AD) pathophysiology. Beta-site APP-cleaving enzyme 1 (BACE1) has been considered as a key regulator of AD pathogenesis by controlling amyloid beta peptide (Aβ) accumulation. In addition, previous studies reported that endoplasmic reticulum (ER) stress and neuroinflammation have been proposed in ethanol-induced neurodegeneration. Thus, we investigated the role of ER stress and PGE, a neuroinflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…As classified by the World Health Organization (WHO), alcohol use is the third-highest health risk factor in developed countries and the greatest risk factor in developing countries, [12] and its aldehydic metabolite, acetaldehyde, is classified as a class I carcinogen [36]. Relevant to our study, epidemiological studies have shown that excessive alcohol consumption is a risk factor for dementia [49] and alcohol intake drives expression levels of amyloid precursor protein (APP) and Aβ-producing enzymes in animal models [21, 27]. Alcohol also increases lipid peroxidation through increased oxidative stress and drives mitochondrial dysfunction [38, 39, 58].…”
Section: Introductionmentioning
confidence: 91%
“…As classified by the World Health Organization (WHO), alcohol use is the third-highest health risk factor in developed countries and the greatest risk factor in developing countries, [12] and its aldehydic metabolite, acetaldehyde, is classified as a class I carcinogen [36]. Relevant to our study, epidemiological studies have shown that excessive alcohol consumption is a risk factor for dementia [49] and alcohol intake drives expression levels of amyloid precursor protein (APP) and Aβ-producing enzymes in animal models [21, 27]. Alcohol also increases lipid peroxidation through increased oxidative stress and drives mitochondrial dysfunction [38, 39, 58].…”
Section: Introductionmentioning
confidence: 91%
“…Exacerbation of AD pathogenesis by alcohol has been reported using both in vitro and in vivo studies. In human, SK-N-MC neuroblastoma cells ethanol upregulated BACE1 expression and Aβ production, as well as increased reactive oxygen species (ROS) production, cyclooxygenase-2 (COX-2) expression and PGE 2 production [ 32 ]. Ethanol exposure of mice for 4 weeks increased APP levels and BACE1 expression, promoted Aβ production, increased plaque deposition, and worsened cognitive deficits [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Alzheimer’s disease (AD), microglial phagocytosis of oligomeric and aggregated forms of amyloid beta (Aβ) is one of the key means by which amyloid burden is limited [ 26 , 27 ]. Several studies suggest that alcohol may be a risk factor for AD [ 28 31 ], and there are also reports that alcohol increases amyloid processing and deposition [ 32 34 ]. However, whether alcohol influences the ability or efficacy of microglial cells to internalize Aβ has not been examined, although several studies have shown that peripheral macrophages have reduced phagocytotic activity after alcohol treatment [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that SXFAD mice deficient in p38 α , and the knockdown of p38 α , leads to enhanced A β degradation by increasing the expression of neprilysin, a metalloproteinase in glial cells [ 94 ]. The activating transcription factor 4 (ATF4) is another factor that enables the activation of proapoptotic proteins of p38 by initiating MKK6 [ 95 ], and p38 helps in binding the Atf4 factor to the CHOP promoter and proceeds in the expression of caspase-4 [ 96 ].…”
Section: The Baseline Of Neuroinflammation In Admentioning
confidence: 99%
“…For the treatment with interferons, the Janus kinase (JAK) is essential for the phosphorylation of STAT factors [100]. The STAT members are diverse in their function and are accounted to play a crucial role in differentiation, proliferation, and cell survival [90][91][92][93][94][95][96][97][98][99][100][101][102][103]. They function as essential mediators in cytokine receptor signaling and are involved in the modulation of transcriptional target genes.…”
Section: Jak-stat Pathwaymentioning
confidence: 99%